ANALISIS PENGARUH IKLAN DAN KREDIBILITAS ENDORSER TERHADAP KESADARAN MEREK UNTUK MENINGKATKAN SIKAP TERHADAP MEREK PRODUK MINUMAN BERSODA MEREK FANTA - Satrya, Danar; Mudiantono, Mudiantono (Faculty of Economics and Business Diponegoro University, 2014)
This study aims to analyze the effects arising from the advertisement and endorser credibility on brand awareness and its impact on brand attitude of the product brand FANTA soda. The variables used in this study is an advertisement and endorser credibility as an independent variable, then the brand awareness as a latent variable and brand attitude as the dependent variable.The samples in this study were 96 respondents are S1 Diponegoro University student who never consume soft drinks brand FANTA. The method used was purposive sampling by distributing questionnaires to the respondents. This study uses quantitative analysis that test reliability and validity test, the classical assumption test, goodness of fit test and multiple linear regression analysis.Based on the results of two-stage regression analysis in this study shows that ad (X1) and the credibility of the endorser (X2) significant effect on brand awareness (Y1) FANTA brand soft drinks products with regression coefficient of 0.226 and 0.305. While brand awareness (Y1) significantly influence the brand attitude (Y2) FANTA brand soft drinks products with regression coefficient of 0.501